1994
DOI: 10.1108/02644409410799407
|View full text |Cite
|
Sign up to set email alerts
|

Parallel computation schemes for dynamic relaxation

Abstract: This paper describes a parallel algorithm for Dynamic Relaxation Method. The basic theory of the Dynamic Relaxation is presented in brief to prepare the reader for the parallel implementation of the algorithm. Some fundamental parallel processing schemes have been explored for the implementation of the algorithm. "Geometric Parallelism" was found suitable for the DR problem on transputer-based syetems. The evolution of the algorithm is given by identifying the steps which could be executed in parallel. The str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 5 publications
0
20
0
Order By: Relevance
“…The method was independently proposed by Day [20] and Otter [21] for the analysis of prestressed concrete pressure vessels, although (as noted by Topping [22]) its con-90 cept was already known by Rayleigh. The method has been extensively used for a wide range of structural problems with both geometric and material non-linearities as for instance, the form finding and load analysis of tension structures [23] where it provides more reliable results in terms of solution convergence if compared to the well known iterative matrix schemes with Newton-Raphson method [24].…”
Section: The Dynamic Relaxation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The method was independently proposed by Day [20] and Otter [21] for the analysis of prestressed concrete pressure vessels, although (as noted by Topping [22]) its con-90 cept was already known by Rayleigh. The method has been extensively used for a wide range of structural problems with both geometric and material non-linearities as for instance, the form finding and load analysis of tension structures [23] where it provides more reliable results in terms of solution convergence if compared to the well known iterative matrix schemes with Newton-Raphson method [24].…”
Section: The Dynamic Relaxation Methodsmentioning
confidence: 99%
“…The method has been extensively used for a wide range of structural problems with both geometric and material non-linearities as for instance, the form finding and load analysis of tension structures [23] where it provides more reliable results in terms of solution convergence if compared to the well known iterative matrix schemes with Newton-Raphson method [24]. More-95 over, the DR does not require assembling/manipulation of a global stiffness matrix, hence it is relatively easy to implement and is highly suitable for parallel computing [22].…”
Section: The Dynamic Relaxation Methodsmentioning
confidence: 99%
“…In contrast with viscous damping, which assumes that connection between the nodes has a viscous force component, kinetic damping is artificial damping with no real effect. Employed successfully by many authors, kinetic damping has been found to be stable and rapidly convergent when dealing with large displacements (Barnes, 1999;Papadrakakis, 1981;Topping and Khan, 1994). When kinetic damping is employed, the viscous damping coefficients in Eq.…”
Section: Fictitious Masses and Kinetic Dampingmentioning
confidence: 97%
“…An iterative process has traditionally been applied to solve these equations of motion for the form-finding of cable-net and membrane structures (Williams 2001;Topping and Iványi, 2008;Adriaenssens et al, 2012;Richardson et al, 2013) with discussions on the effects of the given parameters on convergence also available (Barnes, 1977;Topping and Khan, 1994) and so further elaboration is not needed here. However, a simple example is presented below, implementing the method on the free-form surface show in Fig.20.…”
Section: Grid Relaxationsmentioning
confidence: 99%